2004
DOI: 10.1152/ajplung.00172.2003
|View full text |Cite
|
Sign up to set email alerts
|

DNA synthesis and Bcl-2 expression during development of mucous cell metaplasia in airway epithelium of rats exposed to LPS

Abstract: Tesfaigzi, Yohannes, J. Foster Harris, Jon A. Hotchkiss, and Jack R. Harkema. DNA synthesis and Bcl-2 expression during development of mucous cell metaplasia in airway epithelium of rats exposed to LPS. Am J Physiol Lung Cell Mol Physiol 286: L268-L274, 2004. First published October 3, 2003 10.1152/ ajplung.00172.2003.-Exposure of pulmonary airways to environmental toxins and allergens may cause proliferation of airway epithelial cells and mucous cell metaplasia (MCM); however, it is unclear to what extent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 28 publications
5
55
0
Order By: Relevance
“…In wild-type mice exposed to allergen for 15 days, ER Bax was detected in mucous cells, suggesting that during resolution hyperplastic mucous cells are targeted for removal. Several studies have shown that following injury to the airway epithelium, a large proportion of the hyperplastic and cycling cells are secretory cells (49 -51) and mucous cells arise mainly by self-replication and differentiation of pre-existing cells (52,53). Because mucous cells are the hyperplastic cells, they may be by default susceptible to cell death and elimination in vivo during resolution.…”
Section: Discussionmentioning
confidence: 99%
“…In wild-type mice exposed to allergen for 15 days, ER Bax was detected in mucous cells, suggesting that during resolution hyperplastic mucous cells are targeted for removal. Several studies have shown that following injury to the airway epithelium, a large proportion of the hyperplastic and cycling cells are secretory cells (49 -51) and mucous cells arise mainly by self-replication and differentiation of pre-existing cells (52,53). Because mucous cells are the hyperplastic cells, they may be by default susceptible to cell death and elimination in vivo during resolution.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether goblet cells arise via cell differentiation has been questioned recently. In rat airways exposed to endotoxin, 50% of goblet cells were reported to stain for BrdU, leading the authors to conclude that goblet cells can arise via cell proliferation (63). We suggest that the BrdUpositive goblet cells described by these authors may have arisen via proliferation of precursor cells before differentiation into mucin-containing goblet cells for the following reasons: 1) precursor epithelial cells decide to differentiate while in their most rapid state of proliferation (8); and 2) BrdU was administered continuously from 24 h before to 48 h after endotoxin exposure (63), a time period during which goblet cell precursor cell proliferation and subsequent goblet cell differentiation could occur.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies in animal models suggest that the intrinsic apoptotic pathway that is responsible for removing excess numbers of mucous cells may be dysfunctional in individuals with asthma (15) and cystic fibrosis (20,21). In an effort to determine which of the Bcl-2 family of proteins plays a role in sustaining MCM in chronic bronchitis, we screened for the expression of all Bcl-2 family mRNAs in AECs from patients with chronic bronchitis and control subjects without lung diseases.…”
Section: Exposure To Cigarette Smoke Reduces Bik Expressionmentioning
confidence: 99%
“…The cell death of airway epithelial cells (AECs) during the resolution of metaplastic mucous cells is regulated by the Bcl-2 family of proteins (20,21), and involves the intrinsic apoptotic pathway (22). During the resolution of allergen-induced epithelial and mucous cell hyperplasia that is mediated by IFN-g, we showed that STAT1 and Bik, a proapoptotic Bcl-2 family member, are crucial factors, because unlike wild-type mice, STAT1-and Bik-deficient mice fail to resolve mucous cell metaplasia (MCM).…”
mentioning
confidence: 99%